Bakteri Bacillus Sebagai Agen Kontrol Hayati dan Biostimulan Tanaman - Arkan Setiaji; Raden Roro Rifka Annisa; Deris Trian Rahmandhias (Rekayasa, 2023)
One of the long-term constraints in agricultural productivity is the dependence of farmers on synthetic pesticides. The application of pesticides has a negative impact on ecosystems and human health. Utilization of microorganisms such as bacteria Bacillus as a biological control agent is an alternative to reduce the use of synthetic pesticides. A simpler discussion of the interaction between Bacillus and plants is important to carry out. This article aims to review the mechanism of the role of Bacillus as a biological control agent and growth stimulant in plants. Bacillus is a genus of bacteria that can be used as biological control agents because it is adaptive, capable of forming endospores and tolerant of various environmental conditions. These properties are advantageous in competition with phytopathogens through an antibiosis mechanism in the form of toxin production. Bacillus infection of plants is able to stimulate the emergence of systemic resistance as an initial defense mechanism in plants. Bacillus associated with plants can provide a growth stimulation effect because the metabolites produced are able to trigger the sensitivity of the root system for nutrient absorption and stimulate the regulation of growth regulators such as the synthesis of auxin, gibberellins, and cytokinins. Based on these reviews, the use of based biological agents and biostimulants Bacillus is expected to be able to support global efforts to achieve sustainable development targets, especially in the agricultural sector